Misreporting signs of child abuse: The role of decision‐making and outcome information. Issue 1 (28th November 2013) - Lindholm, Torun; Sjöberg, Rickard L.; Memon, Amina
<x xml:space="preserve">Abstract</x> Two studies provided evidence that a decision to report an ambiguous case of child abuse affected subsequent memory of the case information, such that participants falsely recognized details that were not presented in the original information, but that are schematically associated with child abuse. Moreover, post‐decision information that the child had later died from abuse influenced the memory reports of participants who had chosen not to report the case, increasing their reports of false schema‐consistent details. This suggests that false decision‐consistent memories are primarily due to sense‐making, schematic processing rather than the motivation to justify the decision. The present findings points to an important mechanism by which decision information can become distorted in retrospect, and emphasize the difficulties of improving future decision‐making by contemplating past decisions. The results also indicate that decisions may generate false memories in the apparent absence of external suggestion or misleading information. Implications for decision‐making theory, and applied practices are discussed.